The psychology of parental control : how well-meant parenting backfires - Grolnick, Wendy S. (Mahwah, N.J. : L. Erlbaum Associates, 2003)
What is parental control? Is it positive or negative? Are there alternatives to control and how might we apply them? This book addresses these and other questions about the meaning and predictors of parental control, as well as its consequences for children's adjustment and well-being.
The concept of control -- Fulfilling children's needs : the self-determination view -- The complexity of control : disentangling parenting dimensions -- Overt and covert control -- Differentiating the effects of control : compliance versus internalization -- Control in context -- What makes parents controlling : pressure from above and below -- What makes parents controlling : pressure from within -- Control and academics -- Control and sports -- Conclusions.
Includes bibliographical references (pages 153-167) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Parent and child -- Psychological aspects; Parenting -- Psychological aspects; Control (Psychology); Parents -- Psychology; Parent and child; Child psychology; Parent-Child Relations; Parenting -- psychology; Power, Psychological; Child Behavior; Parents -- psychology; Psychology, Child; Parents et enfants -- Aspect psychologique; Rôle parental -- Aspect psychologique; Contrôle (Psychologie); Parents -- Psychologie; Parents et enfants; Enfants -- Psychologie; FAMILY & RELATIONSHIPS -- Abuse -- Child Abuse; FAMILY & RELATIONSHIPS -- Adoption & Fostering; FAMILY & RELATIONSHIPS -- Parenting -- Parent & Adult Child; FAMILY & RELATIONSHIPS -- Parenting -- General; Parent and child; Child psychology; Control (Psychology); Parent and child -- Psychological aspects; Parenting -- Psychological aspects; Parents -- Psychology; Ouder-kind-relaties.; Dwang; Psychologische aspecten; Toezicht; Ouders